10 Menit Plus Tiap “Tamu Perkasa” Inovasi Integrasi Pendidikan Karakter Bangsa Pada Pelajaran Kejuruan Elektronika di SMK Negeri 2 Kudus - Susanto, Budi (SCAD Independent, 2024)
National character education is learning that absolutely must be given to students, including students in vocational schools, especially since the current shift in national character values ​​is very worrying. The need for this education is to provide filers to students so that moral degradation and a shift in the noble values ​​of the Indonesian nation do not arise. National character education is not only the responsibility of Religion teachers and Civics teachers. National character education must be carried out in total action involving all teachers in all subjects, including vocational practice subjects. The problem of learning national character in vocational subjects is how to integrate it and what is the most appropriate approach to this problem. The 10 Minutes Plus Approach for Each